2020
DOI: 10.1016/j.annemergmed.2020.09.064
|View full text |Cite
|
Sign up to set email alerts
|

54 From the COVID-19 Epicenter: Using Telemedicine to Serve the Needs of the Geriatric Population

Abstract: intervention characteristics from the Consolidated Framework for Implementation Research (CFIR): intervention source, evidence strength and quality, relative advantage, adaptability, trialability, complexity, design quality and packaging, and cost.Results: We identified 18 clinicians who documented ePPE use. On review, 2 never used ePPE and 5 only supervised other clinicians who used ePPE. Of the remaining 11, we interviewed 7 attending physicians and 1 physician assistant between 5/15/20 and 6/5/20. Providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One study described the remote evaluation of patients by an ED (emergency department) provider on a telemedicine platform on a desktop or mobile phone during the local pandemic surge, in northern Manhattan/NYC. 73 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study described the remote evaluation of patients by an ED (emergency department) provider on a telemedicine platform on a desktop or mobile phone during the local pandemic surge, in northern Manhattan/NYC. 73 …”
Section: Resultsmentioning
confidence: 99%
“…11 studies were finally included after reviewing the full texts. [65][66][67][68][69][70][71][72][73][74][75] No additional suitable studies were found after reference screening.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation